Board Empowerment: What Motivates Board Members of Founder-Owned Companies?. (April 2020) - Libman, Alexander; Dolgopyatova, Tatiana; Yakovlev, Andrei
This article investigates the role of boards in founder-managed firms with concentrated ownership in emerging markets. The literature frequently suggests that in this type of companies, boards have little influence on the corporate decision making. The article conducts a case study of AFK Sistema—a large Russian founder-managed firm with concentrated ownership. We observe that, contrary to the expectations, in this company, the founder provided real authority to the board, at the same time focusing on recruiting independent (mainly foreign) members. Based on this case, we argue that selectively empowering boards in this type of ownership setting could be beneficial for the firm: Selective empowerment is a source of intrinsic motivation for the independent board members, making them proactively search for new projects and assist in their implementation on behalf of the firm. As a result, the company can overcome a number of important barriers in its development.